1999
DOI: 10.1023/a:1020761831295
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Hexokinase (HK, EC 2.7.1.1) is a key enzyme in the control of brain glucose metabolism. The regulatory role of HK in different neural cell types has not been elucidated. In this study we determined some kinetic and regulatory properties of HK in mouse cerebrocortical astrocytes in primary culture. Astroglial HK showed an absolute requirement for Mg-ATP and D-glucose. The pH optimum of HK was between 7.4 and 8.0. For astroglial HK, the Km for Mg-ATP was approximately 208 microM and Vmax approximately 35.4 mU/mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…From the astrocyte-to-neuron lactate shuttle hypothesis it follows that the level of glycolysis is required to be higher in astrocytes than neurons and thus hexokinases should be expressed preferentially in astrocytes. Gene expression analysis of FACS sorted pools of cortical neurons and astrocytes showed that both cell types express HK enzymes, as expected ( 33 , 35 , 36 ). However, the qPCR data of the mRNA revealed that the HK1, HK2, and HK3 genes were consistently expressed at a higher level in neurons than in astrocytes ( Fig.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…From the astrocyte-to-neuron lactate shuttle hypothesis it follows that the level of glycolysis is required to be higher in astrocytes than neurons and thus hexokinases should be expressed preferentially in astrocytes. Gene expression analysis of FACS sorted pools of cortical neurons and astrocytes showed that both cell types express HK enzymes, as expected ( 33 , 35 , 36 ). However, the qPCR data of the mRNA revealed that the HK1, HK2, and HK3 genes were consistently expressed at a higher level in neurons than in astrocytes ( Fig.…”
Section: Resultssupporting
confidence: 78%
“…Hexokinases are housekeeping enzymes that catalyze the first step of glycolysis ( 35 , 36 ). Analysis of gene expression in FACS sorted neuron and astrocytes showed that all 3 isoforms of hexokinase (HK1-3) are expressed at higher levels in neurons than astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…3). Furthermore, evidence suggests that hexokinase activity is not significantly different between neurons and glia [65, 66], and that the enzyme has a slower rate (rate-limiting step) compared to uptake and extrusion in neurons [63]. Another potential interpretation is that glial cells do not use 2-NBDG and that upon entering the cell, the glucose analog is readily transported out prior to being phosphorylated by hexokinase.…”
Section: Discussionmentioning
confidence: 99%
“…OeHK , the first rate-limiting enzyme in the glycolytic pathway, was found to be down-regulated in CG. These findings may have implications for assessing glycolytic flux and its regulation in olive oil metabolism ( Lai et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%